Health workers' manual on counselling for maternal and child health. (Western Pacific education in action series, 1995)
Presents substantial information on educating and counseling people to promote healthy behavior among pregnant women and those who have children under the age of five. Provides step-by-step procedures on specific maternal and child health situations. A very useful manual for those who are pregnant, planning to have a baby and for those who have children under five years of age. Uses simple and straightforward words for easy understanding.